2017
DOI: 10.18632/oncotarget.16933
|View full text |Cite
|
Sign up to set email alerts
|

Micrornas in prostate cancer: an overview

Abstract: Prostate cancer is the second highest cause of cancer mortality after lung tumours. In USA it affects about 2.8 million men and the incidence increases with age in many countries. Therefore, early diagnosis is a very important step for patient clinical evaluation and for a selective and efficient therapy. The study of miRNAs' functions and molecular mechanisms has brought new knowledge in biological processes of cancer. In prostate cancer there is a deregulation of several miRNAs that may function as tumour su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 117 publications
1
102
0
2
Order By: Relevance
“…MiRs are short non‐coding RNAs with a length of 18–25 nucleotides that can prevent protein expression through the breakdown of specific target mRNAs or through the inhibition of their translation . MiRs can be detected in urine as a free form, in prostate cancer cells in urinary precipitates and in exosomes.…”
Section: Mir In Urinementioning
confidence: 99%
“…MiRs are short non‐coding RNAs with a length of 18–25 nucleotides that can prevent protein expression through the breakdown of specific target mRNAs or through the inhibition of their translation . MiRs can be detected in urine as a free form, in prostate cancer cells in urinary precipitates and in exosomes.…”
Section: Mir In Urinementioning
confidence: 99%
“…Altered miRNA expression is associated with physiological changes in tumorigenesis and disease progression in PCa (reviewed in (Chun-Jiao, et al 2017;Vanacore, et al 2017)). …”
Section: Dysregulation Of Mirnas In Pcamentioning
confidence: 99%
“…Accumulated evidence indicated that aberrant expression of miRNAs associates with various types of cancer. These dysregulated miRNAs function as either oncogenes or tumor suppressors in carcinogenesis and progression of cancers [8,9]. Thus, to explore the aberrant miRNAs expression in osteosarcoma might lead to the discovery of novel miRNAs biomarkers.…”
mentioning
confidence: 99%